NITRATES IN ISCHEMIC HEART DISEASE TREATMENT, YESTERDAY AND TODAY - S. N. Tereschenko; N. A. Djaiani; E. V. Iljina (Столичная издательская компания, 2015)
The problem of nitrate formulation choice in treatment of patients with ischemic heart disease is reviewed. Importance of development of shortacting nitrates in form of spray, containing nitroglycerin or isosorbid dinitrate, is highlighted. Polycomponent effects of nitrates, ensuring antianginal and antiischemic effect in patients both with stable and acute forms of ischemic heart disease are enumerated. Problem of side effects, frequency of tolerance development in long-term nitrates treatment and tolerance prevention method by interrupted nitrates prescription are analyzed. Wide opportunities of contemporary therapy with nitrates through development of new forms of special drugs, containing isosorbid - 5 - mononitrate in microspheres, are emphasized.